Allergen-Specific Child Immunotherapy: Current State of Affairs - E. A. Vishneva; L. S. Namazova-Baranova; A. A. Alekseeva; L. R. Selimzyanova; J. G. Levina; K. E. Efendieva; E. A. Dobrynina (Педиатрическая фармакология, 2016)
The article is devoted to allergen-specific immunotherapy (ASIT) — the only etiopathogenic therapy method for allergic diseases. By promoting the formation of immunological tolerance, ASIT modifies the course of the disease, prevents the occurrence of new or the worsening of existing sensitizations, thereby preventing the development of asthma, which is especially important for pediatric patients. The authors present the mechanism of action and its main features and conditions with regard to achieving the planned effect. Considered are the key contraindications to ASIT, the principles of selecting the appropriate allergen for the treatment and features of its introduction to both children with mono sensitization and children sensitive to the allergen group. Further prospects of research development and existing achievements of this medical technology are mentioned.